Central overexpression of leptin antagonist reduces wheel running and underscores importance of endogenous leptin receptor activity in energy homeostasis - Matheny, Michael (American Physiological Society, 2009)
We used recombinant adeno-associated virus (rAAV)-mediated gene delivery to overexpress a mutant of rat leptin yielding a protein that acts as a neutral leptin receptor antagonist. The long-term consequences of this overexpression on body weight homeostasis and physical activity, as assessed by voluntary wheel running (WR), were determined in F344 × Brown Norway (BN) rats. Leptin antagonist overexpression was confirmed by examination of mRNA levels in the hypothalamus. Food consumption and body weight gain were exacerbated in the antagonist group during both chow and high-fat feeding periods over the 192-day experiment. In a second experiment, a lower dose of antagonist vector was used that resulted in no change in food consumption but still increased body weight. The degree of antagonist overexpression was sufficient to partially block signal transducer and activator of transcription 3 (STAT3) phosphorylation due to administration of an acute submaximal dose of leptin. Rats were provided free access to running wheels for 4 days during both the chow and high-fat feeding periods. With both antagonist doses and during both chow and high-fat feeding, WR was substantially less with antagonist overexpression. In contrast, when leptin was overexpressed in the hypothalamus, WR activity was increased by greater than twofold. At death, adiposity and serum leptin levels were greater in the antagonist group. These data indicate that submaximal central leptin receptor blockade promotes obesity and diminishes WR activity. These findings underscore the critical role of unrestrained leptin receptor activity in long-term energy homeostasis and suggest that even minor disruption of leptin receptor function can promote obesity.